Advances in Mathematical Economics Volume 16 - Kusuoka, Shigeo; Maruyama, Toru.; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2012)
No Back Cover Text
Keywords: Mathematics; Mathematics; Game Theory, Economics, Social and Behav. Sciences